Comparative analysis between the use of Sodium Chloride and Portland Cement in the stabilization of clay soils on the road linking the areas of the populated centers of Miraflores and Shultin, Baños del Inca district, city of Cajamarca. (LACCEI, 2024)
Worldwide, there are deficiencies in the quality of soils, so the search for materials that function as stabilizing additives arises. This research work presents the analysis and comparison of the influence of Portland Cement type I and Sodium Chloride in clayey soils, applied in proportions of 0.6%, 1.2% and 1.8%, determining the most advantageous material. CBR test were carried out at 95% and 100% DMS obtaining as results of addition of Portland Cement, an increase reaching values of 23.32, 45.33% and 46.31% and 32.82, 47.04 and 50.37%, instead the addition of Sodium Chloride a reduction was observed obtaining values of 6.34, 6.33 and 3.58% and 10.07, 15 and 12.55%. In conclusion, Portland Cement type I achieves a considerable increase in bearing capacity in the percentages proposed, in contrast to Sodium Chloride which showed unfavorable results.